الوصف في شعر البحتري (Journal of Imam Al-Kadhim College, 2023)
This study, tagged with (Description in the Poetry of Al-Buhtari) began with a brief presentation of the poet’s life and the most important poetic purposes in which he organized, and the research consisted of an introduction and two sections. And then I devoted the second topic to talk about the descriptions included in his poetry, such as describing palaces and Riyadh, describing the night and the wolf and others, using adequate models from Al-Buhturi's poetry, concluding the research with the most prominent results that I reached, including the poet's abundance of innovated improvements, and his dependence on linguistic structures, such as addition repetition, etc.; To convey and confirm the poetic image, and to resort to colors and make them meet and blend; To combine his sensory images with imagination, with his selection of words and ideas, relying on imagination, drawing on the data of nature.
Keywords: كلمات مفتاحية : الوصف , شعر , البحتري